Radio Republic of Iraq and Awareness Promoting of Minorities’ Rights - Hamoudi, Safad Hussam (ALBAHITH ALALAMI, 2020)
Proposals to raise awareness of the rights of minorities and secure their freedoms have begun to receive attention Internationally. It is escalated, especially after the increasing impact of wars and conflicts on these situations Minorities, and UNESCO stresses the need to take over information and communication policies Greater attention to protect minority rights. Hence the importance of our research, the problem of which lies in the main question: (What is the role Radio Republic of Iraq has played in promoting awareness of minority rights at the level : Public and Social?) . As one of the Iraqi media networks , laws oblige them to pay attention to the rights of minorities and to spread a culture of pluralism , diversity and acceptance of others in the local community. The researcher designed the questionnaire form in his employee survey In the radio, according to the axes that focused on the mechanisms of program planning in radio ,The Republic of Iraq, and the radio’s treatment of important social issues, The role of the radio in promoting awareness of minority rights was among the conclusions: -The Republic of Iraq Radio relies on its handling of related issues Minorities within their general media context, and do not adopt specific strategies to promote awareness of minority rights. - The radio sets its programmatic plans according to the policies of the media network Al-Iraqi, and the suggestions of some of its affiliates, which happens repeatedly. - Some pressures affect the handling of events related to minorities in Iraq. Among them are the attitudes of employees, and their personal attitudes towards certain segments of those Minorities